Trade and Industrialization - Deepak Nayyar; NAYYAR (Deepak) (Delhi Oxford University Press, 1997)
This collection of essays explores selected themes in trade and industrialization in India, provides critical surveys of the literature, and analyses issues which are the subject matter of intense debate.
Keywords: Economic Development; Stock Market; Industrialization; Technology and Development